Gestão e políticas de educação no contexto da pandemia de Covid-19 (2020-2021): um olhar sobre Minas Gerais, e um pouco mais - Gomides, Bárbara Barra (2022)
The object of study of the present work is the analysis of the management and educational policies implemented in Minas Gerais, in the context of the pandemic caused by the coronavirus (SARS-CoV-2 virus; COVID-19 disease), in the years 2020 and 2021. At the beginning of 2020 in Brazil, due to social isolation during the COVID-19 pandemic, face-to-face classes were suspended, abruptly changing the way education works. This new context was mainly characterized by the mandatory use of technological devices for remote teaching and the absence of effective and egalitarian government responses, compromising the public education network in Minas Gerais. This new system, rooted in a historical marketing capitalist logic, intensified inequalities in Brazil regarding the democratic perspective of access to education. Thus, the present work aimed to contextualize the policies and management of education in Minas Gerais in the period 2020-2021, supported by a theoretical framework that situates the development of the field of education administration in Brazil, and the initial theoretical production on the implications of the coronavirus pandemic on management and education policy in the Brazilian reality. Thus, the dialectical and social understanding of this scenario of inequalities is justified - multidimensional - historically pre-existing and intensified by the pandemic, by the current Brazilian government and above all by the new government of the state of Minas Gerais. For this, it carried out a qualitative, exploratory and analytical study, through documents involving, in a contextualized way, the theme of Educational Management and Policies in Minas Gerais. The search for data was carried out in the SCIELO virtual library (Scientific Electronic Library Online), on the website of the State Department of Education of Minas Gerais, and in books by Benno Sander. According to the results found, it was observed that emergency remote teaching was implemented in a hurry and without considering the multiple Brazilian realities, revealing how much better educational policies need to be planned and implemented, in order to avoid the deepening of existing inequalities. in the country. Many students were “invisible” and having their educational rights denied due to the negligence of public authorities. Failures are clear with regard to the accessibility of technologies, since not all students have the possibilities and the appropriate tools to continue their distance studies. And even those students who have all the technological apparatus, there is still a worrying distance present in the relationship between student and educator, considering that at all levels of education, this relationship and approximation between both is primordial and irreplaceable. In addition, some homes are not considered beneficial to the studies, which further complicates and intensifies the complexity of the problems presented. Given this situation, many students feel unmotivated, excluded from the process, leading to a large and worrying increase in school dropouts. Therefore, the pandemic scenario intensifies and highlights the deepening of social inequalities and the fragility of Brazilian public schools. In view of this, it is necessary to promote reflections on the need for a new model of a fairer society, providing the guarantee of the right to education and quality of teaching. Thus, the epistemological perspective adopted in this work, comprises political, social and economic factors, to identify the challenges and impacts faced in educational management. Thus, making it possible to critically rethink and analyze the educational system and public policies adopted in Brazil, as well as to generate proposals aimed at improving the educational system, from a democratic perspective.